Juridical Review of Singer’s Voice Publicity Rights in AI Use on Digital Media Platform - Sisca Mustika Tiara; Andry Setiawan (Law Research Review Quarterly, 2026)
The development of Artificial Intelligence (AI) has significantly transformed the creative industry. One emerging phenomenon is the use of AI voice cloning technology, which enables the replication of singer's voices without the direct involvement or consent of the original voice owners. This practice raises complex legal issues, particularly concerning the protection of singer's right of publicity as part of their personal and commercial identity. This study examines two primary issues: the juridical review of singer's right of publicity in Indonesia and the forms of legal liability arising from the use of AI on digital media platforms. This research employs a normative juridical method with statutory and conceptual approaches, utilizing primary legal materials in the form of relevant legislation and secondary legal materials derived from legal literature and scientific journals. The results indicate that Indonesia has not yet explicitly regulated the protection of singer's voices as an object of right of publicity. However, legal protection may be afforded through the analogy of existing regulations, namely the Copyright Law (UUHC), the Personal Data Protection Law (UU PDP), and the Electronic Information and Transactions Law (UU ITE), as well as through civil liability mechanisms, including cease and desist notices (somasi) and tort claims based on PMH in accordance with the applicable legal provisions. Given the absence of specific regulations governing publicity rights, amendments to the Copyright Law (UUHC) are necessary to ensure effective legal protection and legal certainty for stakeholders in the creative industry, particularly singers, in the era of artificial intelligence.